“Accidental Victims” of Trial and Investigation: Problem of Keeping Suspects and Defendants in Russian Empire in 1725—1741 - E. V. Borodina (Научный диалог)
The article is devoted to the problem of the arrest of suspects in Russia in 1725—1741. As a result of the analysis of historiography and historical sources, the author came to the conclusion that the history of the court in Russia in the early modern period is inextricably linked with the history of places of detention, since Russian prisons of the 18th century were intended primarily to hold defendants, and not to punish criminals. The study of normative legal acts of the middle of the 17th century — 1741 showed that the arrest as a measure necessary for the timely presentation of litigants to the court was officially stipulated for the first time in the decree “On the form of the court” of November 5, 1723. A comparison of the norms of laws and the actual practice of legal proceedings of central and regional institutions revealed that the institution of arrest of suspects and defendants was not properly regulated. It was a “blind spot” in legislation that led to prison overcrowding. The rule on the arrest of suspects was aggravated by the introduction in the reign of Peter the Great of a revision-decisive procedure for approving sentences and reviewing court cases, which concerned serious crimes, and a significant extent of the territory of Russia.